A state of the art review on geotechnical reinforcement with end life tires - M. Shariati; M. Afrazi; H. Kamyab; S. Rouhanifar; E. Toghroli; M. Safa; Sh. Chelliapan; H. Afrazi (Global Journal of Environmental Science and Management)
This study provides a comprehensive exploration of the utilization of scrap tires in geotechnical engineering, focusing on their applications, mechanical behavior, environmental impact, and potential challenges. The utilization of waste tires in engineering applications is of paramount importance, offering a sustainable solution to the escalating challenge of waste tire management. The accumulation of discarded tires poses significant environmental and economic concerns globally, with traditional disposal methods often leading to environmental degradation, fire hazards, and increased land use. By harnessing the inherent properties of scrap tires, such as their durability and energy-absorbing characteristics, geotechnical engineering presents a promising path for repurposing these materials. This review examines how integrating scrap tires into geotechnical projects, such as retaining walls, slopes, and drainage systems, can offer sustainable alternatives while addressing environmental concerns. The paper extensively analyzes the mechanical behavior of sand-rubber mixtures through laboratory investigations. Factors including rubber proportions, aspect ratios, and interaction mechanisms are dissected to understand their influence on shear strength, deformation behavior, and modulus properties. These insights pave the way for optimizing the performance of sand-rubber mixtures in engineering applications. Additionally, the article delves into modeling approaches that simulate the intricate behavior of these mixtures, facilitating better design and analysis. The economic feasibility of incorporating scrap tires is investigated, emphasizing the cost-effectiveness achieved through reduced material costs and enhanced infrastructure durability. The environmental benefits of diverting rubber waste from landfills are discussed, highlighting the alignment with sustainability goals and regulations. Despite the advantages, engineering challenges associated with rubber particles' behavior are acknowledged, and potential solutions are explored. Through a comprehensive synthesis of research findings and practical implications, this review aims to provide a deep understanding of the potential of scrap tires in geotechnical engineering. It concludes by advocating for further research and innovation to harness the full potential of scrap tires, ultimately contributing to a more sustainable and resilient built environment.